Thai female non-smoker with recurrent lung adenocarcinoma who has dramatic and prolonged response to gefitinib for over one year - Charoentum C. (2014)
A 53-year old non-smoking Thai female was diagnosed with metastatic non-small cell lung cancer to bone. The initial biopsy from the bone lesion showed metastatic adenocarcinoma. She achieved partial response after treatments with radiation therapy to the bones, followed by 6 cycles of combination chemotherapy. About 4 months later, recurrence of the pulmonary and osseous disease was apparent. She has ECOG performance status of 3. Gefitinib 250 mg/day was administered until disease progression for about 14 months. After 6 weeks on this therapy, she had dramatic improvement of all symptoms including her performance status and had nearly complete resolution of all pulmonary lesions. Tolerability was good, with only mild fatigue. The overall survival was 28 months. This illustrates that gefitinib could produce significant clinical benefits in selected Thai patients even with poor performance status. This result is consistent with previous reports that the clinical characteristics of female, non-smoker and adenocarcinoma histology seem to predict response to gefitinib.